2003
DOI: 10.1073/pnas.1735403100
|View full text |Cite
|
Sign up to set email alerts
|

The genome of Nanoarchaeum equitans: Insights into early archaeal evolution and derived parasitism

Abstract: The hyperthermophile Nanoarchaeum equitans is an obligate symbiont growing in coculture with the crenarchaeon Ignicoccus. Ribosomal protein and rRNA-based phylogenies place its branching point early in the archaeal lineage, representing the new archaeal kingdom Nanoarchaeota. The N. equitans genome (490,885 base pairs) encodes the machinery for information processing and repair, but lacks genes for lipid, cofactor, amino acid, or nucleotide biosyntheses. It is the smallest microbial genome sequenced to date, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
409
1
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 472 publications
(427 citation statements)
references
References 49 publications
14
409
1
3
Order By: Relevance
“…The reverse gyrase of the archaeon Nanoarchaeum equitans is atypical because its two modules (helicase and topoisomer- (Waters et al 2003). It was suggested that this organization may correspond to the ancestral form of reverse gyrase, according to the early emergence of N. equitans at the base of the archaeal domain in both SSU rRNA (Huber et al 2002) and concatenated ribosomal protein trees (Waters et al 2003).…”
Section: Phylogeny Of the Reverse Gyrasementioning
confidence: 99%
See 1 more Smart Citation
“…The reverse gyrase of the archaeon Nanoarchaeum equitans is atypical because its two modules (helicase and topoisomer- (Waters et al 2003). It was suggested that this organization may correspond to the ancestral form of reverse gyrase, according to the early emergence of N. equitans at the base of the archaeal domain in both SSU rRNA (Huber et al 2002) and concatenated ribosomal protein trees (Waters et al 2003).…”
Section: Phylogeny Of the Reverse Gyrasementioning
confidence: 99%
“…It was suggested that this organization may correspond to the ancestral form of reverse gyrase, according to the early emergence of N. equitans at the base of the archaeal domain in both SSU rRNA (Huber et al 2002) and concatenated ribosomal protein trees (Waters et al 2003). However, this archaeon emerged as a sister group of Thermococcales in the reverse gyrase tree (BV = 75% and PP = 0.99, Figure 2) in agreement with a revised position of N. equitans based on a recent and more refined phylogenetic analysis of a concatenation of ribosomal proteins (Brochier et al 2005b).…”
Section: Phylogeny Of the Reverse Gyrasementioning
confidence: 99%
“…The DPANN superphylum encompasses the 'Nanoarchaeota' (Waters et al, 2003;Podar et al, 2013), the only DPANN phylum with cultured representatives, as well as the candidate phyla 'Nanohaloarchaeota' (defined from metagenomic assembly (Narasingarao et al, 2012) and SAGs (Ghai et al, 2011) from hypersaline environments); 'Parvarchaeota' (defined from a metagenomic assembly from an acid mine drainage; Baker et al, 2010), 'Aenigmarchaeota' (defined from three SAGs from Homestake mine groundwater seep (Lead, SD, USA) and the Great Boiling Spring sediments; Rinke et al, 2013) and 'Diapherotrites' (defined from SAGs from Homestake mine groundwater seep; Rinke et al, 2013). As such, the DPANN superphylum represents an intriguing collection of phyla with disparate physiological preferences and environmental distribution, ranging from the obligatory symbiotic and thermophilic species within the 'Nanoarchaeota', to the acidophilic candidate phylum 'Parvarachaeota' and to the non-extremophilic candidate phyla 'Aenigmarchaeota' and 'Diapherotrites'.…”
Section: Introductionmentioning
confidence: 99%
“…The organisms chosen were Nanoarchaeum equitans (Waters et al, 2003), Mycoplasma genitalium (Fraser et al, 1995), Schizosaccharomyces pombe (Wood et al, 2002), and the Mimivirus from Entamoeaba (Raoult et al, 2004). The first three model organisms were chosen as representative of the three separate domains of life (Archaea, Eubacteria and Eukarya, respectively), to encompass phylogenetically distant organisms.…”
Section: Methodsmentioning
confidence: 99%